Orthodox Christian Bioethics: Some Foundational Differences from Western Christian Bioethics - Engelhardt, H. Tristram (Studies in Christian ethics, 2011)
Just as the physics of Newton and Einstein are separated by foundationally different paradigms, so that key terms such as time, space, mass, and energy have different meanings in the different physics, this is also the case with respect to the various Christianities. Given different theological frameworks, the ‘same term’ can have different extensions and intensions. This essay explores the implications of the differences in the theological paradigm shaping Orthodox Christianity in contrast to Western Christianity, in particular Roman Catholicism, with a special focus on the differences in the communities’ appreciation of the wrongness of abortion. Using the example of abortion, the contrast between Orthodox Christianity’s noetically grounded approach to moral-theological issues and that which developed in the West and gave centrality to a philosophically shaped moral theology is explored.